El control preventivo de la hacienda pública municipal en la provincia de Entre Ríos - Cosundino, Roberto A. (2019)
Abstract: The work reviews the model of preventive control of administrative acts related mediate or immediately with the public finances of the municipalities of Entre Ríos. First, the concept of preventive control is delimited, and then it is introduced in the analysis of the two municipal control bodies: internal (municipal accounting) and external (Court of Accounts of the province), to conclude with some ideas related to this modality of public control. Between them, and to create an environment conducive to the development of internal preventive control, it is indicated that the municipal accountant must be an autonomous control body, its maximum authority must last eight years in its functions with the possibility of being designated for another period, and in addition, to be named by contest; all this, as does the constitution for the provincial accounting. In relation to the municipal external preventive control, which is currently in the hands of a provincial body, it is indicated that after the last constitutional reform of the Province and in a framework of municipal autonomy, it must necessarily be exercised by a municipal body or entity.